The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1440-1681.2010.05417.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of glycated albumin and fasting plasma glucose improves the detection of diabetes in Chinese subjects

Abstract: SUMMARY1. The aim of the present study was to assess the validity of glycated albumin (GA) and fasting plasma glucose (FPG) as a screening tool for the early detection of diabetes in Chinese subjects.2. A total of 1971 outpatient subjects underwent a 75 g oral glucose tolerance test (OGTT) and GA measurement. The receiver operating characteristic curve (ROC) was plotted to examine the sensitivity, specificity, and positive and negative predictive values of GA and FPG in detecting undiagnosed diabetes at the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
6
26
2
Order By: Relevance
“…In a Japanese population study, the ROC analysis for detecting diabetes identified the GA threshold as 15.5% [23], while another study of Japanese subjects reported a GA level of 17.0% as the lower limit of glucose intolerance [21]. A similar threshold of GA was obtained in a Chinese population study (17.1%) [22]. The thresholds in these studies were in good agreement with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…In a Japanese population study, the ROC analysis for detecting diabetes identified the GA threshold as 15.5% [23], while another study of Japanese subjects reported a GA level of 17.0% as the lower limit of glucose intolerance [21]. A similar threshold of GA was obtained in a Chinese population study (17.1%) [22]. The thresholds in these studies were in good agreement with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…But previous studies showed that FPG alone did not have sufficient sensitivity to detect diabetes [14], [15]. Based on the criteria of FPG≥7.0 mmol/l for diabetes screening, only 63.46% (436/687) of potential diabetes patients were detected in this study, similar with other study in China [16]. If additional OGTT was used for screening, the rest 36.54% potential diabetes cases could be identified.…”
Section: Discussionsupporting
confidence: 78%
“…GA is now widely regarded as a sufficiently accurate reflection of short-term hyperglycemia control (two-week periods) because ALB has a circulating half-life of about 17 days [21]. GA has also been proven useful for distinguishing stress hyperglycemia, and for screening and diagnosing diabetes [22], [23]. Moreover, GA has been reported as a better indicator of glycemic control than HbA1c in hemodialysis patients with end-stage diabetic nephropathy [24].…”
Section: Discussionmentioning
confidence: 99%